2021
DOI: 10.3390/antiox10111854
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Sequencing Analysis in Obstructive Sleep Apnea and Depression: Anti-Oxidant and MAOA-Inhibiting Effects of miR-15b-5p and miR-92b-3p through Targeting PTGS1-NF-κB-SP1 Signaling

Abstract: The aim of this study was to identify novel microRNAs related to obstructive sleep apnea (OSA) characterized by intermittent hypoxia with re-oxygenation (IHR) injury. Illumina MiSeq was used to identify OSA-associated microRNAs, which were validated in an independent cohort. The interaction between candidate microRNA and target genes was detected in the human THP-1, HUVEC, and SH-SY5Y cell lines. Next-generation sequencing analysis identified 22 differentially expressed miRs (12 up-regulated and 10 down-regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…At the same time, they showed increased LBP and I-FABP levels indicating more bacterial translocation and 'leaky gut' [56]. Furthermore, increased intestinal permeability in non-obese males with OSA (as compared to non-OSA subjects) showed significant associations with inflammatory mediators (serum IL-1β) [53], and zonulin levels in OSA patients correlated positively with some metabolic, inflammation and hepatic parameters [6]. Interestingly, OSAS children showed increased severity of inflammation and gut barrier damage-related strains as compared to healthy population [57].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…At the same time, they showed increased LBP and I-FABP levels indicating more bacterial translocation and 'leaky gut' [56]. Furthermore, increased intestinal permeability in non-obese males with OSA (as compared to non-OSA subjects) showed significant associations with inflammatory mediators (serum IL-1β) [53], and zonulin levels in OSA patients correlated positively with some metabolic, inflammation and hepatic parameters [6]. Interestingly, OSAS children showed increased severity of inflammation and gut barrier damage-related strains as compared to healthy population [57].…”
Section: Discussionmentioning
confidence: 91%
“…Its prevalence is increasing worldwide [3,4]. Metabolic disorders are in particular closely associated with OSA syndrome (OSAS) which is a chronic disorder characterized by intermittent hypoxia during sleep with re-oxygenation injury [5,6]. In fact, more than two thirds of people with OSA is at least overweight and weight loss helps reduce OSA severity or attenuate other symptoms (reviewed in [7]).…”
Section: Introductionmentioning
confidence: 99%
“…40 Previous studies focusing on genetic factors also found two microRNAs (viz., miR-15b-5p and miR-92b-3p) that may modify OSA-related depression. 41 On the other hand, compared with individuals without SB, SB patients were found to have higher scores of depression. 42 SB has long been known to be regulated centrally, and depression is considered a potential aetiology of SB 16 .…”
Section: Discussionmentioning
confidence: 97%
“…Available evidence suggests that OSA may lead to the development or exacerbation of depressive symptoms by initiating or amplifying the pathologic processes of cerebral small vessel disease and blood–brain barrier dysfunction 40 . Previous studies focusing on genetic factors also found two microRNAs (viz., miR‐15b‐5p and miR‐92b‐3p) that may modify OSA‐related depression 41 . On the other hand, compared with individuals without SB, SB patients were found to have higher scores of depression 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The potential of miR-499 as a biomarker of OSA has been also evaluated, with higher levels identified in a population with OSA than in control patients [41 ▪ ]. Similarly, Chen et al [42 ▪ ] identified 22 differentially expressed miRNAs that regulate important genomic pathways, such as cellular senescence, the cell cycle and adherents junctions. Furthermore, the miRNA profile was characterized by IH with reoxygenation injury.…”
Section: Micrornas In Obstructive Sleep Apnoeamentioning
confidence: 99%